The development of undernourished children: an experimental study on early feeding - Pollitt, Ernesto (2000)
The study was a randomized clinical tria! involving two cohorts (12 and 18 months) of nutritionally at risk Jndonesian children and three types of supplementary feeding: high energy and micronutrients; skimmed milk and micronutrients; and skimmed milk. The hypothesis of the study was that high energy and micronutrient supplements given early to children could delay on physical growing and mental development. The results showed that a combined energy and micronutrient supplement given for ayear to the 12-month-old children had wide range beneficia! effects. The same supplement given to the 18-month-old had only a modest effect. This suggests that if such an intervention is to he effective it needs to begin early in life.